Customary Criminal Penalties for Violations of Local Customary Obligations for Adultery Offender: An Effort to Achieve Culture-Based Legal Compliance - Dahlan, Arteria; Brouwer, Darryl Evan; Tangkau, Daniel Julian (Faculty of Law, Universitas Pekalongan, 2024)
In the Indonesian legal system, customary legal System has been recognized as one of its components. In the National Criminal Code, customary punishment has been stipulated as one of the additional punishments. As an additional punishment, there is no obligation for the judge to punish the defendant with additional punishment. Moreover, The National Criminal Code has also criminalized adultery as a criminal offense. It is an offense institutionalized from the Adat Law recognized in certain regions in Indonesia. There are some regions in Indonesia where many forms of adultery are recognized as customary criminal law. Hence, it is possible to enforce culture based legal obedience on adat community, specifically on adultery offense. The enforcement of culture based legal compliance could increase the effectivity of criminal justice system. This article aims to analyze the legal issue regarding customary punishment towards adultery as a means to enforce culture based legal compliance among community. The research method applied in this article is normative legal research. This article concludes that since adultery is recognized as customary offense in some regions, the customary punishment in the National Criminal Code should be treated as an imperative punishment by the judge in order to enforce legal compliance culture.